The Influence of Corporate Social Responsibility on Values Companies in the Coal Subsector Companies Listed on the Indonesia Stock Exchange for the 2020-2024 Period - Adelia Emmanuella Hutahaean; Jadongan Sijabat; E. Manatap Berliana Lumban Gaol (JURNAL ECONOMINA, 2026)
This study aims to analyze the effect of Corporate Social Responsibility on firm value in coal mining sub-sector companies listed on the Indonesia Stock Exchange during the period 2020-2024. The study is based on stakeholder theory, which emphasize that companies are responsible not only to stakeholders but also to all stakeholders. The research employs a quantitative method using secondary data obtained from financial statements, annual reports, and sustainability reports. The sampling technique used is purposive sampling, resulting in 13 companies with a total of 65 observations. Data were analyzed using simple linear regression with the assistance of SPSS version 26. The results indicate that Corporate Social Responsibility has a positive and significant effect on firm value with a significance value of 0.024. the Adjusted R Square value of 0.063 indicates that Corporate Social Responsibility explains 6,3 % of the variation is explained by other factors outside the research model. Therefore, the higher the level of Corporate Social Responsibility disclosure, the higher the firm value.